The CMC_E Project: an e-Learning environment to develop foreign language competence in companies - Menezes, Helena (2009)
The project Communicating in Multilingual Contexts meets the Enterprises aims to find out if there is shortages of foreign languages in companies in the regions where the partners of the project are located and provides a virtual learning environment offering language learning materials in six different languages thus opening up opportunities for better trained, and thus more competitive, future and in-service employees. A needs analysis survey of foreign language competences in companies was carried out in order to identify the key language competences commonly required by different sectors of the labour market and design relevant language materials. These materials are being piloted in order to assess their efficiency and reformulate minor issues. This paper presents the project, relevant data from the survey, the materials designed and the first results of the piloting phase.